Dynamics of the Reaction S(1D) + HD, H2, and D2: Isotopic Branching Ratios and Translational Energy Release. Issue 4 (1994) - Inagaki, Yousuke; Shamsuddin, Sayed Mohammed; Matsumi, Yutaka; Kawasaki, Masahiro
Abstract : Doppler profiles of H and D atoms from the reaction S( 1 D) with HD and a 1:1 mixture of H2 and D2 have been measured by a laser-induced fluorescence technique with a vacuum ultraviolet laser. An isotopic channel branching ratio of φ (SD + H)/φ (SH + D) is measured to be 0.9 ± 0.1 in the reaction of S( 1 D) + HD at average collision energy Ecoll = 1.2 kcal/mol. In S( 1 D) + HD, D2, and H2, the translational energies released are almost the same, 4.6 ± 0.5 kcal/mol for H and D production channels. The measured branching ratio and translational energy release suggest that the reaction proceeds via a long-lived complex formed by insertion.